Scientific Attitudes, Activities and Learning Outcomes of Student in Material of Fungi Using Predict Observe Explain (Poe) Model Based on Bioedutainment - Widyanigrum, Dewi; Bintari, Siti Harnina; Rahayuningsih, Margareta (FMIPA UNNES, 2018)
This study aims to determine the effectiveness of POE model based on bioedutainmentimplementation in material of fungi towards activity, scientific attitude and learning outcome of VII grade students. This study uses a one-shot case study research design. The population of this study is students of class VII SMPN 1 Secang, while the sample is students of class VII B. The hypothesis used is that POE method based on bioedutainment is effective towards the learning outcome of the students.  The sample was taken by purposive sampling method. POE based on bioedutainment was applied to the sample class by using game elements in each POE syntax. The results of this study indicate the percentage of student activity is 83% and the percentage of their scientific attitude is 70% in the category of good and very good. The result of student learning completeness is 70% with an average value of 80.33. The teacher's response stated that students became active and enthusiastic about learning. The conclusion of the study is that the POE model based on bioedutainment is effective towards the activity, scientific attitude, and learning outcome of the students.